Decolonization of Peruvian education: an epistemological look towards teacher training - Oyola Gaspar, Emperatriz Karina (2024)
In Latin America, epistemological knowledge and approaches come from an external, hegemonic power group. Decolonizing education requires an insurgency against Eurocentric knowledge and ideology, considering aspects inherent to Andean worldview and ancestral culture; rewriting and reconstructing our epistemological bases towards teacher training to achieve positive educational content and form. Decolonization enables the attainment of a society with fewer inequality gaps. In Peruvian education and that of other Latin American countries, the influence of dominant Westernism is evident, hindering the emergence of epistemologies that could strengthen education. It is crucial to respect the plurality of Southern epistemologies and educational complexity. The reconstruction of Andean epistemology is a path towards the decolonization of Peruvian education.